Islet prohormone processing in health and disease. (19th September 2018) - Chen, Yi‐Chun; Taylor, Austin J.; Verchere, C. Bruce
Abstract : Biosynthesis of peptide hormones by pancreatic islet endocrine cells is a tightly orchestrated process that is critical for metabolic homeostasis. Like neuroendocrine peptides, insulin and other islet hormones are first synthesized as larger precursor molecules that are processed to their mature secreted products through a series of proteolytic cleavages, mediated by the prohormone convertases Pc1/3 and Pc2, and carboxypeptidase E. Additional posttranslational modifications including C‐terminal amidation of the β‐cell peptide islet amyloid polypeptide (IAPP) by peptidyl‐glycine α‐amidating monooxygenase (Pam) may also occur. Genome‐wide association studies (GWAS) have showed genetic linkage of these processing enzymes to obesity, β‐cell dysfunction, and type 2 diabetes (T2D), pointing to their important roles in metabolism and blood glucose regulation. In both type 1 diabetes (T1D) and T2D, and in the face of metabolic or inflammatory stresses, islet prohormone processing may become impaired; indeed elevated proinsulin:insulin (PI:I) ratios are a hallmark of the β‐cell dysfunction in T2D. Recent studies suggest that genetic or acquired defects in proIAPP processing may lead to the production and secretion of incompletely processed forms of proIAPP that could contribute to T2D pathogenesis, and additionally that impaired processing of both PI and proIAPP may be characteristic of β‐cell dysfunction in T1D. In islet α‐cells, the prohormone proglucagon is normally processed to bioactive glucagon by Pc2 but may express Pc1/3 under certain conditions leading to production of GLP‐1(7‐36NH2 ). A better understanding of how β‐cell processing of PI and proIAPP, as well as α‐cell processing of proglucagon, are impacted by genetic susceptibility and in the face of diabetogenic stresses, may lead to new therapeutic approaches for improving islet function in diabetes.